Brief historical description of the sociology of health - Balarezo-López, Gunther Naldo (2022)
A bibliographic review was made over the published literature on the relationship between social sciences, specifically sociology and medicine. For this, various publications were analyzed and the most relevant aspects were summarized. The objective was to reflect on the emergence of the sociology of health as a discipline, and its relationship with medicine, given that despite the fact that the disease has always been linked to sociocultural aspects, it was not until the middle of the last century that medicine recognizes the importance of sociology in explaining the health-disease process. Even so, sociologists were rarely part of a multidisciplinary team with medical professionals. Currently, sociologists participate with medical professionals in research, to explain health problems that affect people.